Analisis Laporan Keuangan Pt Goto Indonesia Tbk 2022-2023 - Nabilah, Dhiya Nasywa; Setiawan, Eby Khoirunnisa; Permana, Kania Dewita; Kalishara, Kariima Monica; Putra, Angga Sanita (Peneliti.net, 2025)
This study aims to evaluate and analyze the performance of PT. GOTO Gojek Tokopedia Tbk. The company's financial performance is analyzed based on four main aspects: liquidity, solvency, activity, and profitability. The research employs a descriptive qualitative method by collecting data through the documentation of PT. GOTO Gojek Tokopedia Tbk's financial reports for the 2022-2023 period. Data analysis is conducted using financial ratio calculations across these four aspects. The results indicate that PT. GOTO Gojek Tokopedia Tbk's financial performance in terms of liquidity ratios was in good condition but experienced a decline in 2023. Solvency showed an increase, although it was not significant. Similarly, profitability was highly satisfactory, as it exceeded the industry standard of over 30%.